Hepatitis C virus dynamics with viral load and ALT and biopsy-free liver damage monitoring (2006)
The reduced standard model of three populations (healthy and diseased hepatocytes, and viral load) for the study of hepatitis C virus (HCV) dynamics is compared with the model of viral dynamics with alanine aminotransferase (ALT). In terms of the threshold parameter that is the same for both models, the existence and stability of the endemic equilibrium state is determined, as well as the overall stability of the healthy individual's equilibrium state. On the other hand, an experimental study is presented that shows that it is possible to monitor liver damage without biopsies, by numerical estimation of the model parameters, considering only measurements of viral load, ALT levels and a reasonable assessment of liver damage pretreatment.